Understanding the variability of clear-sky outgoing long-wave radiation based on ship-based temperature and water vapour measurements - John, Viju Oommen; Buehler, Stefan; von Engeln, A.; Eriksson, P.; Kuhn, Thomas; Brocard, E.; Koenig-Langlo, G. (Quarterly Journal of the Royal Meteorological Society, 2006)
High-resolution radiative transfer model calculations with the Atmospheric Radiative Transfer Simulator (ARTS) were used to simulate the clear-sky outgoing long-wave radiative flux (OLR) at the top of the atmosphere. The unique set of radiosonde data collected by the research vessel Polarstern of the Alfred Wegener Institute for Polar and Marine Research during 27 expeditions in the years 1982 to 2003 was used to investigate the sources of clear-sky OLR variability for ocean areas in different climate zones and seasons. For this dataset, tropospheric temperature variations contribute approximately 33 W m(-2) OLR variability. tropospheric relative humidity variations 8.5 W m(-2), and vertical structure 2.3-3.4 W m(-2). Of these, 0.3-1.0 W m(-2) are due to structures on a vertical scale smaller than 4 km, which cannot be resolved by conventional remote-sensing instruments. It was also found that the poor absolute accuracy of current humidity data in the upper troposphere, approximately 40% relative error in relative humidity, leads to a significant uncertainty in OLR of about 3.8 W m(-2) (for a midlatitude summer atmosphere), which should be put in the context of the double CO2 effect of only 2.6 W m(-2) (for the same atmosphere). Validerad; 2006; 20070427 (pafi)